PEO + NaSCN and ionic liquid based polymer electrolyte for supercapacitor. (2021) - Manfo T, Azemtsop; Konwar, Subhrajit; Singh, Pramod K.; Mehra, R.M.; Kumar, Yogesh; Gupta, Meenal
Abstract: In this study, initially ion conducting solid polymer electrolyte films (SPEs) based on polyethylene oxide (PEO) and sodium thiocyanate (NaSCN) have been prepared using the standard solution cast technique. For further enhancement in the ionic conductivity value of optimized film, an ionic liquid (IL; 1-ethyl-3-methyl-imidazolium tricyanomethanide) ([EMIM][TCM]) has been incorporated in different weight ratios into the optimized polymer-salt complex matrix. The prepared SPEs are free-standing, flexible and exhibit good thermal and mechanical stabilities. Polarized optical microscopy (POM) shows a change in the surface morphology of IL doped polymer electrolyte films. The composition nature of polymer electrolyte films was confirmed using fourier transform infrared spectroscopy (FT-IR) via studying ion-ion and ion-polymer interactions. The FTIR studies confirm that complexation occurs between polymer-salt and polymer-salt-ionic liquid interactions. Polymer electrolyte films have been also characterized using X-Ray Diffraction (XRD). The structural analysis confirms that the intensity of crystalline peaks existing in solid polymer electrolyte films decreases after doping IL which enhances its amorphous nature. The thermal stability of different prepared electrolyte films has been investigated using thermogravinometric analysis (TGA). Ionic liquid doped polymer electrolyte films show more stable behavior than polymer host PEO and polymer-salt complex at high temperatures. IL doped polymer electrolyte film shows reduction in the degradation process with a residue mass of 29% at 400 °C. Polymer electrolyte films were also characterized using impedance spectroscopy (IS) to check their electrical properties. The maximum ionic conductivity is found to be 8.44 × 10 −5 S cm −1 for 4 wt% IL doped solid polymer electrolyte film and the calculated value of ionic transference number (tion ) for optimized electrolyte film is 0.98. Using this maximum ion-conducting polymer electrolyte film, we have developed a electrical double layer capacitor (EDLC). The calculated value of the specific capacitance of prepared EDLC is 1.07 Fg −1 .